2005
DOI: 10.1177/0310057x0503300611
|View full text |Cite
|
Sign up to set email alerts
|

Debriefing after Critical Incidents for Anaesthetic Trainees

Abstract: This survey investigated the need, and the availability, of debriefing after critical incidents for training anaesthetists. A cross-sectional postal survey of all Australian anaesthetic trainees was conducted in May 2002. Four hundred and nineteen responses were analysed (response rate 64%). Debriefing after a critical incident was perceived by most trainees to be useful, however 36% (n=149) had never been debriefed. Trainees ranked their preferred content for a debriefing as 'anaesthetic issues' followed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 12 publications
0
25
0
2
Order By: Relevance
“…19 Our results indicate that despite the value placed on PRD by health care providors, PRD in Canadian pediatric EDs is underdeveloped, infrequently used, and insufficiently supported. Although there is growing evidence of the positive effect of debriefing after surgical, anesthetic, or critical care-based simulation events, [20][21][22][23][24][25][26][27][28] there is a lack of evidence on how PRD impacts teamwork and patient care in the ED. Our findings are consistent with an Australian study of pediatric ED physicians and nurses that identified a perceived need but a lack of a structured debriefing process.…”
Section: Current Practice and Identified Obstaclesmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Our results indicate that despite the value placed on PRD by health care providors, PRD in Canadian pediatric EDs is underdeveloped, infrequently used, and insufficiently supported. Although there is growing evidence of the positive effect of debriefing after surgical, anesthetic, or critical care-based simulation events, [20][21][22][23][24][25][26][27][28] there is a lack of evidence on how PRD impacts teamwork and patient care in the ED. Our findings are consistent with an Australian study of pediatric ED physicians and nurses that identified a perceived need but a lack of a structured debriefing process.…”
Section: Current Practice and Identified Obstaclesmentioning
confidence: 99%
“…The effectiveness of debriefing on achieving learning objectives has been studied, mostly outside the ED. [20][21][22][23][24][25][26][27][28] Simulation provides an active learning environment for health care providers to experience clinical situations and use cognitive, technical, and affective skills, such as those used in real-life resuscitation scenarios. 7,35 Systematic reviews of simulation literature identified feedback as the most important feature of simulation-based medical education.…”
Section: Training In Debriefingmentioning
confidence: 99%
“…Anesthesia departments in developing countries should have protocol or guidelines on how to deal with catastrophes affecting both consultant and trainee anesthetists. [ 17 18 ]…”
Section: Subsequent Actions or Delayed Actionsmentioning
confidence: 99%
“…If the time is taken to debrief after normal events, then debriefing is more likely to happen after critical events 20) . In a study by Tan 29) , a postal survey was conducted after debriefing of critical incidents for anesthetic trainees. Debriefing after a critical incident was perceived by most trainees to be useful.…”
Section: Debriefing To Improve Clinical Outcomesmentioning
confidence: 99%